2002
DOI: 10.1091/mbc.01-08-0409
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adaptor Complex AP-3 in Targeting Wild-Type and Mutated CD63 to Lysosomes

Abstract: CD63 is a lysosomal membrane protein that belongs to the tetraspanin family. Its carboxyterminal cytoplasmic tail sequence contains the lysosomal targeting motif GYEVM. Strong, tyrosine-dependent interaction of the wild-type carboxyterminal tail of CD63 with the AP-3 adaptor subunit μ3 was observed using a yeast two-hybrid system. The strength of interaction of mutated tail sequences with μ3 correlated with the degree of lysosomal localization of similarly mutated human CD63 molecules in stably transfected nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
204
0
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(229 citation statements)
references
References 66 publications
(79 reference statements)
15
204
0
10
Order By: Relevance
“…These results suggest that a significant pool of PI4KII␣ is controlled by the function of the adaptor complex AP-3. We note that PI4KII␣ was reported to interact with CD63 (Berditchevski et al, 1997;Yauch and Hemler, 2000), a membrane protein of lysosomes proposed to be sorted by AP-3-dependent mechanisms (Rous et al, 2002). Thus, it is possible that a direct or indirect interaction with CD63 may account, at least in part, for the localization of PI4KII␣ in AP-3-derived vesicles.…”
Section: Discussionmentioning
confidence: 82%
“…These results suggest that a significant pool of PI4KII␣ is controlled by the function of the adaptor complex AP-3. We note that PI4KII␣ was reported to interact with CD63 (Berditchevski et al, 1997;Yauch and Hemler, 2000), a membrane protein of lysosomes proposed to be sorted by AP-3-dependent mechanisms (Rous et al, 2002). Thus, it is possible that a direct or indirect interaction with CD63 may account, at least in part, for the localization of PI4KII␣ in AP-3-derived vesicles.…”
Section: Discussionmentioning
confidence: 82%
“…Previous work had shown that OCRL localizes to endosomes and the TGN (Ungewickell et al, 2004;Lowe, 2005). CVAK104 overlapped also significantly with the adaptor protein complex AP3, which is involved in the sorting of lysosomal membrane proteins (Le Borgne et al, 1998;Rous et al, 2002) (Figure 4C). In contrast, very little colocalization of CVAK104 with early endosomal markers such as early endosomal antigen (EEA)1 ( Figure 4C) and rab5 (our unpublished data) was seen.…”
Section: Tissue Expression and Subcellular Localization Of Cvak104mentioning
confidence: 74%
“…20 Therefore, we hypothesized that NE precursor (proNE) is routed to granules through the protein-delivery pathway of CD63, which recruits AP-3 adaptor complex through the C-terminal lysosomal targeting motif GYEVM. 21 Thus, cooperation with CD63 was thought to facilitate the secretory lysosome targeting of proNE.To corroborate our hypothesis, we examined whether CD63 and proNE interacted upon coexpression in COS cells. Furthermore, we examined how CD63 depletion affected proNE trafficking.…”
mentioning
confidence: 74%
“…The CD63AEVM mutant has a single amino acid mutation in the C-terminal lysosomal sorting sequence that decreases intracellular CD63 and plasma membrane sorting. 21 Although not formally proved, CD63AEVM might produce nonfunctional complexes that are likely to be degraded or become transferred to the plasma membrane.In the 5 clones investigated, CD63 siRNA expression showed a mean of 6.5-fold (the range was from 16-fold to 3.7-fold) suppression of CD63 mRNA compared with wild-type cells, CD63 siRNA mock, or a reverted CD63siRNA clone ( Figure 5A). The CD63 mRNA levels of 5 cell clones with scrambled siRNA control vector did not differ from wild-type cells ( Figure S2A).…”
mentioning
confidence: 99%